Examining the Role of Women's Interpersonal Facilitators in Spousal Addiction: A Qualitative Study - Shokri , Alieh; Younesi , Seyed Jalal; Zare Bahramabadi , Mehdi (Psychology of Woman Journal, 2025)
Objective: This study aimed to examine the role of women's interpersonal facilitators in their husbands' addiction.Methods and Materials: The present research employed a qualitative method based on interpretative phenomenological analysis (IPA). Twenty-six married women residing in Tehran were purposefully selected for participation. These women had sought counseling and psychotherapy services in Tehran due to their husbands' drug addiction, with the husbands having over a year of substance abuse history. Interviews were analyzed using the Dickelmann’s interpretative phenomenological analysis approach.Findings: The examination of participants' lived experiences revealed one main theme and five subthemes (interpersonal-multidimensional facilitators: lack of love, disrupted sexual interaction, disturbed emotional interaction, unrealistic expectations, and family-of-origin factors related to the woman).Conclusion: Identifying these factors enhances knowledge and awareness regarding the reasons and mechanisms behind women's roles in their husbands' substance use, as well as its persistence and exacerbation. The findings indicate that focusing on women and improving specific intrapersonal and interpersonal aspects could complement preventive and therapeutic programs for male addiction.